PENGARUH CAPITAL INTENSITY, KOMITE AUDIT DAN KONEKSI POLITIK TERHADAP AGRESIVITAS PAJAK - Nor Aini; Dinar Ambarita (Publika Citra Media, 2026)
This study aims to obtain empirical evidence regarding the influence of Capital Intensity, Audit Committee, and Political Connections on Tax Aggressiveness. This research is a quantitative associative study. The population in this study comprises energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The sample was selected using a purposive sampling method. A total of 13 companies were selected as the research sample, resulting in 65 observation data points. Data were processed using Microsoft Office Excel and EViews 13 statistical software, with analysis including descriptive statistics, model selection tests, classical assumption tests, coefficient of determination, panel data regression analysis, F-statistic test, and t-statistic test. The results of the study indicate that Capital Intensity, Audit Committee, and Political Connections simultaneously have an influence on Tax Aggressiveness. The t-statistic test results show that Capital Intensity has a negative partial effect on Tax Aggressiveness, and the Audit Committee has a positive partial effect on Tax Aggressiveness. Meanwhile, Political Connections do not have a significant effect on Tax Aggressiveness.